Impact of COVID-19 on cancer service delivery: results from an international survey of oncology clinicians. Issue 6 (1st December 2020) - Chazan, Grace; Franchini, Fanny; Alexander, Marliese; Banerjee, Susana; Mileshkin, Linda; Blinman, Prunella; Zielinski, Rob; Karikios, Deme; Pavlakis, Nick; Peters, Solange; Lordick, Florian; Ball, David; et al.
Abstract : Objectives: To report clinician-perceived changes to cancer service delivery in response to COVID-19. Design: Multidisciplinary Australasian cancer clinician survey in collaboration with the European Society of Medical Oncology. Setting: Between May and June 2020 clinicians from 70 countries were surveyed; majority from Europe (n=196; 39%) with 1846 COVID-19 cases per million people, Australia (AUS)/New Zealand (NZ) (n=188; 38%) with 267/236 per million and Asia (n=75; 15%) with 121 per million at time of survey distribution. Participants: Medical oncologists (n=372; 74%), radiation oncologists (n=91; 18%) and surgical oncologists (n=38; 8%). Results: Eighty-nine per cent of clinicians reported altering clinical practices; more commonly among those with versus without patients diagnosed with COVID-19 (n=142; 93% vs n=225; 86%, p=0.03) but regardless of community transmission levels (p=0.26). More European clinicians (n=111; 66.1%) had treated patients diagnosed with COVID-19 compared with Asia (n=20; 27.8%) and AUS/NZ (n=8; 4.8%), p<0.001. Many clinicians (n=307; 71.4%) reported concerns that reduced access to standard treatments during the pandemic would negatively impact patient survival. The reported proportion of consultations using telehealth increased by 7.7-fold, with 25.1% (n=108) of clinicians concerned that patient survival would be worse due to this increase. Clinicians reviewed a median of 10 fewer outpatients/week (including non-face to face) compared with prior to the pandemic, translating to 5010 fewer specialist oncology visits per week among the surveyed group. Mental health was negatively impacted for 52.6% (n=190) of clinicians. Conclusion: Clinicians reported widespread changes to oncology services, in regions of both high and low COVID-19 case numbers. Clinician concerns of potential negative impacts on patient outcomes warrant objective assessment, with system and policy implications for healthcare delivery at large.